2019
DOI: 10.3390/nu11081897
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Food Safety Knowledge and Behaviors of Cancer Patients Receiving Treatment

Abstract: Cancer patients receiving treatment are at a higher risk for the acquisition of foodborne illness than the general population. Despite this, few studies have assessed the food safety behaviors, attitudes, risk perceptions, and food acquisition behaviors of this population. Further, no studies have, yet, quantified the food safety knowledge of these patients. This study aims to fill these gaps in the literature by administering a thorough questionnaire to cancer patients seeking treatment in three hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Handling leftovers was the topic that the dietetics students had the least understanding of in this study. This is of concern because the high-risk patients report low understanding of leftover handling [9,23] and would benefit of the advice by their dietitians. In fact, the leftover handling was identified as one of the major knowledge gaps among cancer patients receiving treatment in the USA [9] and the UK [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Handling leftovers was the topic that the dietetics students had the least understanding of in this study. This is of concern because the high-risk patients report low understanding of leftover handling [9,23] and would benefit of the advice by their dietitians. In fact, the leftover handling was identified as one of the major knowledge gaps among cancer patients receiving treatment in the USA [9] and the UK [23].…”
Section: Discussionmentioning
confidence: 99%
“…This is of concern because the high-risk patients report low understanding of leftover handling [9,23] and would benefit of the advice by their dietitians. In fact, the leftover handling was identified as one of the major knowledge gaps among cancer patients receiving treatment in the USA [9] and the UK [23]. Preventing prolonged storage of RTE food products is vital, particularly among vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with previous studies, which found that patients with cancer need to receive understandable and timely information about FN, and the potential impact of neutropenia and infections on chemotherapy delays or dose modifications. 19 Paden et al 22 similarly reported that patients with cancer with insufficient food safety knowledge expressed negative attitudes toward some aspects of food safety. To improve patients' knowledge, attitude, and behaviors regarding central venous catheter management, existing research supports implementing effective education programs to foster greater self-care abilities and positive self-care management attitudes through face-to-face instruction and discussion, training, and feedback from nurses.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to other research, which has reported that poor or insufficient knowledge can influence a lack of awareness or low-risk perceptions, negative attitudes, lack of confidence in self-management skills, or low motivation to implement self-care behavior among patients with cancer. 22,30 Adherence to dietary, personal, oral, and hand hygiene; home environmental cleaning; pet care and safety; activities and social interactions; and FN management practices are of paramount importance among patients with cancer receiving chemotherapy. 15,[31][32][33] The factors influencing infection prevention practice were evaluated with multiple regression analysis, revealing that knowledge and attitude were concomitant predictors of practice toward infection prevention.…”
Section: Discussionmentioning
confidence: 99%